(untitled) (Scientific journal of the Fergana State University, 2024)
The paper investigates geometry and its manifolds on subspaces, a five-dimensional pseudo-Euclidean space of index two. Geometry in the sphere of real radius is defined. The existence of all hyperbolic spaces of dimension three and some four-dimensional hyperbolic spaces is proved, as well as a manifold of maximum dimension.